Iron-based catalyst with iron loaded on TiCN surface and application of iron-based catalyst in synthesis of ammonia
By using titanium and nitrogen co-doped carbon material (TiCN) as a support, the iron-based catalyst is prepared and the dual-active center catalyst is constructed, which solves the problem of high energy consumption of traditional catalysts under high temperature and high pressure, and achieves the effect of under mild conditions Highly efficient catalytic synthesis of ammonia, with high catalytic activity, stability and safety performance.
Patent Information
- Application Number
- CN202411628189.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the synthetic ammonia industry consumes high energy, and traditional iron catalysts operate under high temperature and high pressure, resulting in large energy consumption and poor catalytic performance, making it difficult to achieve efficient ammonia synthesis under mild conditions.
The iron-based catalyst was prepared by using titanium and nitrogen co-doped carbon material (TiCN) supported by Fe to construct a dual-active central catalyst between the nitrogen vacancy of the support and the Fe surface for catalyzing the ammonia synthesis reaction.
It has achieved efficient catalytic synthesis of ammonia under mild conditions, and the catalyst catalytic activity reaches the Ru-based catalyst level under normal pressure, and has high stability and safety performance, reducing energy consumption.
Smart Images

Figure BDA0005135255380000061 
Figure BDA0005135255380000071 
Figure BDA0005135255380000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to an iron-based catalyst in which iron is loaded on the surface of TiCN and application of the catalyst in synthesizing ammonia. Background Art
[0002] The synthetic ammonia industry is one of the most important chemical industries, and countries around the world are committed to the development of the synthetic ammonia industry. Synthetic ammonia is an effective means of artificial nitrogen fixation, providing 40-60% of the nitrogen source for the human body. Ammonia is easily liquefied (0.86MPa at 20℃ or -33.4℃ at 0.1MPa) and does not contain carbon, so ammonia is regarded as a renewable fuel that is closest to practical use, and is also considered an important hydrogen energy carrier that can coordinate energy and environmental issues. In 1913, Haber-Bosch's ammonia synthesis iron catalyst and its process flow were first industrialized in Oppau, Germany, which evolved the synthesis method of ammonia from cyanide to nitrogen-hydrogen mixed gas synthesis, thereby greatly increasing the yield of ammonia and was hailed as the first generation of ammonia synthesis catalyst. The operating conditions of this process are generally at high temperatures of 400-600°C and high pressures of 20-100MPa, which consumes a lot of energy, causing the synthetic ammonia industry to consume 1% of the world's energy consumption. Therefore, developing a catalyst with high performance under mild conditions to replace traditional iron catalysts is not only a need to improve the traditional Haber-Bosch process, but also a need to meet the challenges of future ammonia new energy. Summary of the invention
[0003] In order to solve the above problems existing in the prior art, the present invention uses titanium and nitrogen co-doped carbon material (TiCN) as a carrier to load Fe to prepare an iron-based catalyst, and constructs a dual-active center catalyst of carrier nitrogen vacancies and Fe surface for catalytic synthesis of ammonia. Carbon material as a basic carrier can provide a large specific surface area, which is not only conducive to the regulation of titanium and nitrogen doping and nitrogen doping forms, but also conducive to the dispersion of titanium / nitrogen and the increase of the number of titanium / nitrogen active sites; nitrogen-doped carbon can promote the transfer of electrons from the carrier to the metal, which is conducive to the activation of N2 / H2 molecules on the metal surface and the synthesis of ammonia; in the TiCN carrier, the nitrogen doping form is rich, not only graphite nitrogen, pyridine nitrogen and pyrrole nitrogen combined with carbon elements, but also ionic nitrogen coordinated with Ti; doped titanium can be reduced, which can accelerate the migration of hydrogen atoms on the surface of the metal catalyst to the carrier, increase the hydrogenation rate of N2 at the nitrogen vacancy and the synthesis of ammonia when overflow hydrogen atoms are combined with lattice nitrogen, and Ti doping can significantly improve the stability of the carrier under the conditions of synthetic ammonia. These characteristics of the TiCN carrier provide a good basis for improving the catalytic performance of iron-based catalysts in synthesizing ammonia.
[0004] The technical solution provided by the present invention is specifically as follows:
[0005] An iron-based catalyst in which iron is loaded on the surface of a titanium and nitrogen co-doped carbon material (TiCN), with TiCN as a carrier, and the active ingredient iron loaded on the surface of TiCN, wherein the mass fraction of iron in the iron-based catalyst is 1%-60%, and the specific surface area of TiCN is 50-500m 2 / g.
[0006] Preferably, the TiCN is prepared by the following method: a Ti precursor, a N precursor and a C precursor having a molar ratio of Ti, N and C of (0.01-0.1): (0.1-0.5): 1 are mixed (preferably, the molar ratio of Ti, N and C is 0.05:0.25:1), and after heating and fusing, the mixture is transferred to a nitrogen atmosphere and calcined (preferably, after heating and fusing at 110°C, the mixture is transferred to a nitrogen atmosphere and calcined at 700°C for 2h).
[0007] Preferably, the Ti precursor is one or more of Ti oxides, hydroxides, organic complexes, and salts, the N precursor is an organic substance containing N, and the C precursor is an organic substance containing C.
[0008] In the preparation process of TiCN carrier, according to the different precursors of Ti, N and C, one or more mixtures of solvents such as water, alcohols, supercritical CO2, etc. that can dissolve or disperse the corresponding precursors can be selected, or a specific proportion of precursors can be heated and melted at a certain temperature without using a solvent. The reaction temperature is preferably between 50-220°C, and more preferably between 80-120°C. The total reaction time from the beginning of heating and melting to the end of the reaction is preferably 1 to 5h, and the preferred reaction time is 1 to 3h; if the reaction time is too short, the precursors of Ti, N and C are not mixed evenly, and the ideal carrier cannot be obtained. The fully mixed sample is transferred to a tubular furnace and heated by programmed temperature increase in an inert atmosphere. The heating rate is preferably 1°C min -1 ~10℃min -1 between 3℃min -1 ~8℃min -1 The reaction temperature is preferably between 500-900°C, more preferably between 650-800°C. The total reaction time from the start of the program temperature rise to the end of the reaction is preferably 3-10 hours, and the preferred reaction time is 3-8 hours; if the reaction time is too short, the precursors of Ti, N and C will not react fully and the ideal carrier cannot be obtained; if the reaction time is too long, the energy consumption of the synthesis process will increase.
[0009] The present invention also provides a method for preparing the iron-based catalyst, comprising the following steps: dispersing a carrier in an iron precursor solution, wherein the mass ratio of iron in the iron precursor solution to the mass ratio of the TiCN carrier is 0.01 to 1.5, stirring and then spinning the solvent to dryness, placing the resulting mixture in a quartz tube, heating it to 300-500° C., and treating it in a reducing gas atmosphere for 2-10 hours to obtain the iron-based catalyst.
[0010] The iron loading rate on the TiCN surface is 1% to 150% of the mass of the TiCN carrier; if the loading rate is lower than 1%, the catalytic effect of the catalyst on synthetic ammonia is not obvious; if the iron loading rate is higher than 150%, the iron particle size will be too large, reducing the catalytic efficiency per unit iron.
[0011] Preferably, the iron precursor is Fe3(CO) 12 , Fe(CH3COCHCOCH3)3, Fe(C5H5)2, Fe(NO3)3, FeCl3, one or more of them.
[0012] The present invention also provides an iron-based catalyst, on which a promoter is loaded.
[0013] Preferably, on the basis of the iron loaded on the TiCN surface, the catalytic performance of the catalyst is improved by adding an appropriate amount of an alkali metal compound, an alkaline earth metal compound, or a mixture of one or more of a rare earth metal compound as an auxiliary agent. The ratio of the appropriate amount of the auxiliary agent added to the molar number of iron loaded on the TiCN surface is 0.1 to 5, and more preferably, the ratio of the amount of the auxiliary agent added to the molar number of iron loaded on the TiCN surface is 0.2. Adding a small amount of auxiliary metal compound is conducive to the distribution of the auxiliary agent around the active iron nanoparticles, thereby effectively promoting the catalytic performance of iron. The addition amount is not more than 5 times the molar number of iron loaded on the TiCN surface, in order to avoid the iron nanoparticles on the catalyst surface being completely covered by the auxiliary agent, thereby hindering the reactants from contacting with the iron surface atoms and reducing their catalytic activity.
[0014] Preferably, the alkali metal compound is one or more of sodium acetate, potassium acetate, rubidium acetate, cesium acetate, sodium nitrate, potassium nitrate, rubidium nitrate, and cesium nitrate; the alkaline earth metal compound is one or more of calcium acetate, barium acetate, strontium acetate, calcium nitrate, barium nitrate, and strontium nitrate; the rare earth metal compound is one or more of lanthanum acetate, samarium acetate, cerium acetate, lanthanum nitrate, samarium nitrate, and cerium nitrate.
[0015] The auxiliary metal compound can also be NaOH, KOH, RbOH, CsOH, CaO, SrO, BaO, La2O3, CeO2 or Sm2O3.
[0016] The method for preparing the iron-based catalyst loaded with a promoter metal compound comprises the following steps: immersing the iron-based catalyst in a solution containing the promoter metal compound, removing the solvent and then drying to obtain the iron-based catalyst loaded with the promoter.
[0017] The present invention also provides the use of the iron-based catalyst in ammonia synthesis reaction. The reaction conditions when the catalyst is used in the ammonia synthesis catalytic reaction are: temperature 250-500°C, pressure 0.1-5.1MPa, space velocity 1000-1000000·h -1 .
[0018] The present invention utilizes the catalyst to react N2 and H2 to generate ammonia at a certain temperature, pressure and space velocity. The temperature of the ammonia synthesis reaction is preferably set within the range of 250-500°C. The reaction temperature is higher than 250°C to ensure that the activation rate of iron-catalyzed nitrogen molecules is fast enough. In addition, the reaction temperature is set below 500°C to prevent the degradation of the iron active component. The pressure of the synthetic ammonia reaction is preferably set within the range of 0.1 to 5.1 MPa. A pressure higher than 0.1 MPa is conducive to the reverse shift of the reaction equilibrium toward ammonia generation. A pressure not higher than 5.1 MPa can save energy consumption caused by pressure increase. The space velocity (GHSV) of the synthetic ammonia reaction is preferably selected to be 1000 to 1000000·h -1 The GHSV is set at 1000 h -1 The above can effectively prevent the generated ammonia from being decomposed into nitrogen and hydrogen again. The GHSV is set at 1000000·h -1 Hereinafter, the energy consumed for circulating the unreacted gas can be saved.
[0019] The principle of the present invention is as follows:
[0020] The present invention uses carbon material as a basic carrier, which can provide a larger specific surface area, which is not only conducive to the regulation of titanium and nitrogen doping and nitrogen doping forms, but also conducive to the dispersion of titanium / nitrogen and the increase of the number of titanium / nitrogen active sites; nitrogen-doped carbon can promote the transfer of electrons from the carrier to the metal, which is conducive to the activation of N2 / H2 molecules on the metal surface; in the TiCN carrier, the nitrogen doping forms are rich, including not only graphitic nitrogen, pyridine nitrogen and pyrrole nitrogen combined with carbon elements, but also ionic nitrogen coordinated with Ti; the doped titanium is reducible, which can accelerate the migration of hydrogen atoms on the surface of the metal catalyst to the carrier, increase the rate of hydrogenation of N2 at nitrogen vacancies and the combination of overflow hydrogen atoms with lattice nitrogen, and can also form coordination with nitrogen elements to increase the stability of the carbon material under synthetic ammonia conditions.
[0021] The present invention has the following advantages and beneficial effects:
[0022] (1) The preparation method of the present invention is simple, and the synthetic ammonia catalyst carrier can be prepared by a simple "one-pot method";
[0023] (2) The catalyst prepared by the present invention forms a TiNX active center through coordination between Ti and N. This active center can synthesize ammonia through the Mars-van Krevelen mechanism under the conditions of synthetic ammonia. At the same time, the iron loaded on the catalyst surface can also serve as an active center to promote the synthesis of ammonia, forming a dual active center, thus constructing a dual active center catalyst of carrier nitrogen vacancies and Fe surface.
[0024] (3) The titanium in the catalyst carrier prepared by the present invention is reducible, which can accelerate the migration of hydrogen atoms on the surface of the metal catalyst to the carrier, increase the rate of hydrogenation of N2 at nitrogen vacancies and the combination of overflow hydrogen atoms with lattice nitrogen, and also form coordination with nitrogen to increase the stability of the carbon material under synthetic ammonia conditions.
[0025] (4) The catalytic activity of the synthetic ammonia catalyst prepared by the present invention can reach the level of Ru-based catalysts under normal pressure, and has high catalytic activity, good stability and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the TiCN carrier obtained in Example 1;
[0027] Figure 2 The XRD pattern of the TiCN carrier obtained in Example 1;
[0028] Figure 3 This is the XPS spectrum of the TiCN carrier obtained in Example 1;
[0029] Figure 4 TEM spectrum of the Fe / TiCN catalyst obtained in Example 1;
[0030] Figure 5 This is a diagram showing the catalytic stability test effect of the catalyst prepared in Example 2. DETAILED DESCRIPTION
[0031] The present invention will be described in detail below with the help of examples. These examples do not limit the protection scope of the present invention in any way, and any equivalent results or equivalent process changes made by using the content and ideas of the present invention specification, or directly or indirectly applying them to other related fields, are also included in the protection scope of the present invention.
[0032] Embodiment 1:
[0033] Preparation of TiCN support
[0034] (1) Take 3 g of anhydrous glucose and 5 g of urea and heat them to 110 °C at a rate of 5 °C / min to melt. Then stir for 30 min and add 1 mL of tetrabutyl titanate (1 g / cm 3 ), and keep stirring, and cool it after the addition is completed.
[0035] (2) The mixture obtained in (1) was cooled and transferred to a tube furnace and heated at 5°C min under a nitrogen atmosphere. -1 The temperature was raised to 700°C at a rate of , then maintained at 700°C for 2h and cooled in the furnace.
[0036] (3) Grinding the black substance obtained in step (2) to obtain a TiCN carrier, the SEM spectrum of which is as follows: Figure 1 As shown, the specific surface area is 201m 2 / g, the larger specific surface area is conducive to the dispersion of iron on its surface. The obtained product was analyzed by XRD and XPS. The results of XRD are as follows Figure 2 As shown in the figure, there is only one bulge peak attributed to C, and no diffraction peak of Ti appears. Figure 3 The XPS results show the presence of Ti, which indicates that Ti is doped into the carrier in the carbon material and that the Ti element is well dispersed in the carbon material.
[0037] Preparation of iron-based catalysts
[0038] (1) Weigh 3.62 g of ferric chloride hexahydrate and dissolve it in 10 mL of ethanol solution. After the ferric chloride hexahydrate is dissolved, add 1.00 g of the obtained TiCN support, stir for 5 h, and then rotary evaporate for 3 h to obtain a mixture.
[0039] (2) The mixture obtained in the previous step was placed in a quartz tube and heated to 500°C at a rate of 5°C / min under a H2 atmosphere. Fe was reduced at 500°C for 4 h to obtain the TEM spectrum of the iron-based catalyst. Figure 4 shown.
[0040] (3) The iron-based catalyst was granulated, and 0.100 g of the iron-based catalyst with a particle size ranging from 0.22 to 0.45 μm was taken and placed in a quartz tube for catalytic activity testing.
[0041] Ammonia synthesis catalyzed by iron-based catalysts
[0042] The rate of ammonia synthesis is calculated by using the method of sulfuric acid absorbing ammonia and the change in sulfuric acid conductivity.
[0043] Pour 200 mL of sulfuric acid solution (c(H2SO4)=0.002 mol / L) into a 500 mL three-necked flask, adjust the stirrer speed to 30 rpm, and adjust the water bath temperature to 30°C.
[0044] H2 / N2 was introduced at a gas flow rate ratio of 3:1, H2: 45 mL / min, N2: 15 mL / min, and the space velocity was 24000·h -1 , the pressure is 0.1MPa. After activation at 400℃ for 3h, the catalytic activity is measured at different temperature points. After reaching each test temperature point, it is stabilized for 30min and then tested again. The test time is 30min. The test results are shown in Table 1 below.
[0045] Table 1 Ammonia synthesis rate at different test temperatures (μmol·g -1 cat ·h -1 )
[0046]
[0047] Example 2: Stability test of Fe / TiCN catalyst
[0048] (1) Weigh 3.62 g of ferric chloride hexahydrate and dissolve it in 10 mL of ethanol solution. After the ferric chloride hexahydrate is dissolved, add 1.00 g of the TiCN carrier obtained in Example 1, stir for 5 h, and then rotary evaporate for 3 h to obtain a mixture.
[0049] (2) The mixture obtained in the previous step was placed in a quartz tube, and the temperature was raised to 500°C at a rate of 5°C / min. Fe was reduced in a H2 atmosphere for 4 hours to obtain an iron-based catalyst.
[0050] (3) The iron-based catalyst was granulated, and 0.100 g of the iron-based catalyst with a particle size ranging from 0.22 to 0.45 μm was taken and placed in a quartz tube for catalytic activity testing.
[0051] Stability test of iron-based catalyst for ammonia synthesis
[0052] The rate of ammonia synthesis is calculated by using the method of sulfuric acid absorbing ammonia and the change in sulfuric acid conductivity.
[0053] Pour 200 mL of sulfuric acid solution (c(H2SO4) = 0.002 mol / L) into a 500 mL three-necked flask, adjust the stirrer speed to 30 rpm, and the water bath temperature to 30°C. Pass H2 / N2 at a gas flow rate of 3:1, H2: 45 mL / min, N2: 15 mL / min, and a space velocity of 24000·h -1 , the pressure is 0.1MPa. The temperature is raised to 400℃ and activated for 3h. Then the stability test is carried out at 400℃ for 24h. The ammonia synthesis rate is tested for 30min every 2h. The stability test results are as follows: Figure 5 As shown, it can be seen that the ammonia synthesis rate has not changed significantly and the catalyst performance is stable.
[0054] Example 3: Ammonia synthesis activity test of iron-based catalysts with different loading rates
[0055] (1) 3.21 g, 3.94 g, 4.83 g and 5.90 g of ferric chloride hexahydrate were respectively weighed and dissolved in 10 mL of ethanol solution. After the ferric chloride hexahydrate was dissolved, 1.00 g of the TiCN carrier obtained in Example 1 was added, and the mixture was stirred for 5 h and then rotary evaporated for 3 h to obtain a mixture.
[0056] (2) The mixture obtained in step (1) is placed in a quartz tube, the temperature is raised to 500°C at a rate of 5°C / min, and Fe is reduced under a H2 atmosphere for 4 hours to obtain iron-based catalysts with iron mass contents of 40wt%, 45wt%, 50wt% and 55wt%, respectively.
[0057] (3) The iron-based catalyst was granulated, and 0.100 g of the iron-based catalyst with a particle size ranging from 0.22 to 0.45 μm was taken and placed in a quartz tube for catalytic activity testing.
[0058] The rate of ammonia synthesis is calculated by using the method of sulfuric acid absorbing ammonia and the change in sulfuric acid conductivity.
[0059] Pour 200 mL of sulfuric acid solution (c(H2SO4)=0.002 mol / L) into a 500 mL three-necked flask, adjust the stirrer speed to 30 rpm, and set the water bath temperature to 30°C.
[0060] H2 / N2 was introduced at a gas flow rate ratio of 3:1, H2: 45 mL / min, N2: 15 mL / min, and the space velocity was 24000·h -1 , the pressure is 0.1MPa. After reduction at 400℃ for 3h, the ammonia synthesis rate of the catalyst at 400℃ was tested for 30min. The test results are shown in Table 2 below.
[0061] Table 2 Ammonia synthesis rate (μmol·g) of catalysts with different Fe mass percentage contents (40wt%~55wt%Fe) -1 cat ·h -1 )
[0062]
[0063] Example 4: Preparation of an iron-based catalyst with KNO3 additive
[0064] (1) 3.62 g of ferric chloride hexahydrate was dissolved in 10 mL of ethanol solution. After the ferric chloride hexahydrate was dissolved, 1.00 g of the TiCN carrier obtained in Example 1 was added, and the mixture was obtained by stirring for 5 h and then rotary evaporation for 3 h. The mixture obtained in the previous step was placed in a quartz tube, heated to 500° C. at a rate of 5° C. / min, and reduced Fe under a H2 atmosphere for 4 h to obtain an iron-based catalyst.
[0065] (2) Weigh KNO3 at a molar ratio of auxiliary agent:Fe=0.2:1, add 10 mL of distilled water, and after it dissolves, add 0.200 g of iron-based catalyst, stir for 3 h, and then rotary evaporate to obtain a mixture.
[0066] (3) The mixture obtained in the previous step was granulated, and 0.1005 g of the catalyst with a particle size ranging from 0.22 to 0.45 μm was taken and placed in a quartz tube for catalytic activity testing.
[0067] The rate of ammonia synthesis is calculated by using the method of sulfuric acid absorbing ammonia and the change in sulfuric acid conductivity.
[0068] Pour 200 mL of sulfuric acid solution (c(H2SO4) = 0.002 mol / L) into a 500 mL three-necked flask, adjust the stirrer speed to 30 rpm, and the water bath temperature to 30°C. Pass H2 / N2 at a gas flow rate ratio of 3:1, H2: 45 mL / min, N2: 15 mL / min, and a space velocity of 24000·h -1 , the pressure is 0.1MPa. After activation at 400℃ for 3h, the catalytic activity was measured at different temperature points. At each test temperature point, it was stabilized for 30min and then tested for 30min. The test results are shown in Table 3 below.
[0069] Table 3 Ammonia synthesis rate of catalysts with KNO3 additive (μmol·g -1 cat ·h -1 )
[0070]
Claims
1. An iron-based catalyst in which iron is supported on the surface of a carbon material TiCN co-doped with titanium and nitrogen, characterized in that: The iron-based catalyst uses TiCN as a carrier, and the surface of TiCN is loaded with active ingredient iron. The mass percentage of iron in the iron-based catalyst is 1%-60%, and the specific surface area of the TiCN is 50-500 m 2 / g.
2. The iron-based catalyst according to claim 1, characterized in that The TiCN is prepared by the following method: a Ti precursor, a N precursor and a C precursor having a molar ratio of Ti, N and C of (0.01-0.1): (0.1-0.5): 1 are mixed, and after heating and fusing, the mixture is transferred to a nitrogen atmosphere for calcination.
3. The iron-based catalyst according to claim 2, characterized in that The Ti precursor is one or more of Ti oxides, hydroxides, organic complexes, and salt compounds; the N precursor is an organic substance containing N, and the C precursor is an organic substance containing C.
4. A method for preparing the iron-based catalyst according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: dispersing a TiCN carrier in an iron precursor solution, wherein the mass ratio of iron to TiCN in the iron precursor solution is 0.01-1.5, stirring and then spinning off the solvent, placing the obtained mixture in a quartz tube, heating it to 300-500° C., and treating it in a reducing gas atmosphere for 2-10 h to obtain the iron-based catalyst.
5. The preparation method according to claim 4, characterized in that: The iron precursor is Fe3(CO) 12 , Fe(CH3COCHCOCH3)3, Fe(C5H5)2, Fe(NO3)3, FeCl3, one or more of them.
6. An iron-based catalyst, characterized in that A promoter is loaded on the iron-based catalyst described in any one of claims 1 to 3.
7. The iron-based catalyst according to claim 6, characterized in that The auxiliary agent is derived from a metal compound, and the metal compound is one or more of an alkali metal compound, an alkaline earth metal compound, and a rare earth metal compound. The molar ratio of the auxiliary agent metal compound to Fe is (0.1-5):
1.
8. The iron-based catalyst according to claim 7, characterized in that The alkali metal compound is one or more of sodium acetate, potassium acetate, rubidium acetate, cesium acetate, sodium nitrate, potassium nitrate, rubidium nitrate, and cesium nitrate; the alkaline earth metal compound is one or more of calcium acetate, barium acetate, strontium acetate, calcium nitrate, barium nitrate, and strontium nitrate; the rare earth metal compound is one or more of lanthanum acetate, samarium acetate, cerium acetate, lanthanum nitrate, samarium nitrate, and cerium nitrate.
9. Use of the iron-based catalyst according to any one of claims 1 to 3, 6 to 8 or the iron-based catalyst prepared by the method according to claim 4 or 5 in the field of synthetic ammonia, characterized in that: As a catalytic material, it catalyzes the reaction of hydrogen and nitrogen to synthesize ammonia.
10. The use according to claim 9, characterized in that: The catalytic reaction conditions for synthesizing ammonia are: temperature 250-500°C, pressure 0.1-5.1 MPa, space velocity 1000-1000000·h -1 .